Structure, Function, and Regulation of the Blood-Brain Barrier Tight Junction in Central Nervous System Disorders - Lochhead, Jeffrey J.; Yang, Junzhi; Ronaldson, Patrick T.; Davis, Thomas P. (Frontiers in Physiology, 2020)
The blood-brain barrier (BBB) allows the brain to selectively import nutrients and energy critical to neuronal function while simultaneously excluding neurotoxic substances from the peripheral circulation. In contrast to the highly permeable vasculature present in most organs that reside outside of the central nervous system (CNS), the BBB exhibits a high transendothelial electrical resistance along with a low rate of transcytosis and greatly restricted paracellular permeability. The property of low paracellular permeability is controlled by tight junction protein complexes that seal the paracellular route between apposing brain microvascular endothelial cells. Although tight junction protein complexes are principal contributors to physical barrier properties, they are not static in nature. Rather, tight junction protein complexes are highly dynamic structures where expression and/or localization of individual constituent proteins can be modified in response to pathophysiological stressors. These stressors induce modifications to tight junction protein complexes that involve de novo synthesis of new protein or discrete trafficking mechanisms. Such responsiveness of BBB tight junctions to diseases indicates that these protein complexes are critical for maintenance of CNS homeostasis. In fulfillment of this vital role, BBB tight junctions are also a major obstacle to therapeutic drug delivery to the brain. There is an opportunity to overcome this substantial obstacle and optimize neuropharmacology via acquisition of a detailed understanding of BBB tight junction structure, function, and regulation. In this review, we discuss physiological characteristics of tight junction protein complexes and how these properties regulate delivery of therapeutics to the CNS for treatment of neurological diseases. Specifically, we will discuss modulation of tight junction structure, function, and regulation both in the context of disease states and in the setting of pharmacotherapy. In particular, we will highlight how these properties can be potentially manipulated at the molecular level to increase CNS drug levels via paracellular transport to the brain.